Putting the Third Wave into Practice: Democracy Promotion in Kenya. (19th December 2016) - Harbeson, John W.
Abstract: Joel Barkan's work as the U.S. Agency for International Development's Regional Democracy and Governance Advisor for Eastern and Southern Africa brought both realism and conceptual strengthening to democracy promotion, most notably giving legitimacy and practical meaning to the concept of civil society as an essential dimension of democratization. Résumé: Le travail de Joel Barkan à l'organisation internationale de développement démocratique régionale et conseiller en gouvernance pour l'Afrique de l'est et du sud a apporté réalisme et renforcement conceptuel à la promotion de la démocratie, notamment en donnant légitimité et sens pratique au concept de la société civile comme une dimension essentielle à la démocratisation.